Solve for x and y: xy-6y+6=0;3xy-5y-8=0

Asked by Anjali Sahu | 28th May, 2013, 01:34: PM

Expert Answer:

xy-6y+6=0;3xy-5y-8=0     
Let xy = u 
Hence, u-6y+6=0;3u-5y-8=0     
Multiply the first equation by 3
3u - 18y + 18 = 0 
And subtract it from the second equation above
13y -26 = 0
y = 2
Substituting the value of y in first equation 
u = 6
xy = 6
x = 3

Answered by  | 28th May, 2013, 05:02: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.